New Practices for a New Day: Principal Professional Development to Support Performance Cultures in Schools (LEARNing Landscapes, 2015)
This study focuses on principal professional development in one school system in the United States to support a performance culture. With the leadership of the superintendent and central office leaders, principal learning communities were established to foster shared learning and professional development that enhanced their roles as lead learners in their buildings. Three primary themes emerged from the research: Beliefs Matter Only if Growth Matters, Transformational Professional Development Builds a Performance Culture, and Effective Professional Development Provides Safe Landing Change. The themes support that leading is learning. The implications of the research lie primarily in the realm of practice.
Keywords: educational leadership; principal; performance culture; leading; learning; practice; professional development; change